(untitled) (Damascus University Journal for the economic and Political sciences, 2021)
People first coined gold dinars and silver dirhams as intermediaries for exchange.Then these coins faded and were replaced by paper money in their phases.At a later stage, bank money of all kinds emerged - without dispensing with paper money, and each of these coins is what distinguishes it from others. However many forms and types of money, the Islamic Sharia came with controls, obliged taxpayers to take into account when cashing or exchanging cash for cash, in order to protect them from falling into usury. Today, he appeared on the trading domin - On a small scale - the so-called electronic money, the best known so-called Bitcoin. The researcher shows in the research what are the popular money types and their source and value and its description by jurisprudence, and then make a total comparison between them and the so-called electronic money, to reach through this comparison to the extent to the possibility of conformity of the provisions, controls and standards set by the scholars for money popular on emergency money (electronic) . Thus, we get an answer to the question posed today: Is it valid to trade what is called today electronic money as cash under the provisions of Islamic law? Thus, is it valid to conclude an exchange contract between them and other money?